2018
DOI: 10.1371/journal.pone.0208689
|View full text |Cite
|
Sign up to set email alerts
|

High HIV incidence and low uptake of HIV prevention services: The context of risk for young male adults prior to DREAMS in rural KwaZulu-Natal, South Africa

Abstract: BackgroundYoung men are less likely than young women to engage with HIV prevention and care, and their HIV-related mortality is higher. We describe HIV incidence and uptake of HIV services in men 20–29 years(y) in rural KwaZulu-Natal, South Africa, before the roll-out of DREAMS.MethodsWe used data from a population-based demographic and HIV surveillance cohort. HIV incidence was estimated from anonymised testing in an annual serosurvey. Service uptake was assessed in 2011 and 2015, through two self-reported ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 29 publications
0
57
1
Order By: Relevance
“…Although, our data suggest gender of sexual partners may be related to the frequency of behavior. Prior studies found HIV testing behavior was significantly associated with sexual practices, but anal sexual practices were pooled with oral under an all-inclusive category [38][39][40] or the studies only evaluated anal sex [41,42]. In Cameroon, prior HIV testing was associated with having 4 or more oral or anal sexual partners in the past year as compared to 1 to 3 sexual partners, but this association was not stratified by sexual practice [40].…”
Section: Plos Onementioning
confidence: 99%
“…Although, our data suggest gender of sexual partners may be related to the frequency of behavior. Prior studies found HIV testing behavior was significantly associated with sexual practices, but anal sexual practices were pooled with oral under an all-inclusive category [38][39][40] or the studies only evaluated anal sex [41,42]. In Cameroon, prior HIV testing was associated with having 4 or more oral or anal sexual partners in the past year as compared to 1 to 3 sexual partners, but this association was not stratified by sexual practice [40].…”
Section: Plos Onementioning
confidence: 99%
“…The study area of ~ 500 km 2 with a population of ~ 17000 16-29 year-olds was the site of the scale-up of structural and behavioural interventions through the DREAMS partnership between 2016 and 2018 [7]. The study area is mostly rural and poorer than most other parts of South Africa, with high levels of unemployment and a high burden of HIV [1,9,23].…”
Section: Settingmentioning
confidence: 99%
“…The evaluation data arose from: (i) surveys with a representative sample of 13-35-year-old-males and females (n = 4918); (ii) rapid ethnographic community mapping (n = 4); (iii) provider and user interviews (n = 22 and n = 58 respectively); and (iv) group discussions (n = 29). Detailed methods and ndings of the contextual factors that drive risk and create barriers to effective HIV testing, care and prevention have been previously reported [1,6,9,15,[25][26][27][28]. For the purposes of the intervention development the ndings were summarised and converted into vignettes, case-studies and simple infographics by a team of social scientists, statisticians and clinicians who had been engaged in the data collection and peernavigator training.…”
Section: Participatory Intervention Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to HIV diagnostic and testing services is not readily available to many rural and sub-urban dwellers. For instance, KwaZulu-Natal province in South Africa, has been known for its high incidence and prevalence of HIV [3][4][5][6] and the region is also known for low uptake of HIV prevention services [7]. Precise and efficient diagnosis of any disease, coupled with the appropriate treatments, will result in proper control [8].…”
Section: Introductionmentioning
confidence: 99%